UJI DOSIS PUPUK NPK PADA BEBERAPA VARIETAS PADI UNGGUL BARUEFFECT OF NPK FERTILIZER DOSAGES ON SOME NEW VARIETIES OF RICE PLANT (Oryza saliva L.)) - D. DARYANTI; TYAS SUMARAH KURNIA DEWI (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2009)
The research was done in Kelurahan Kauman Kidul, Kecamatan Sidorejo, Kota salatiga, from February until June 2008, the type of soil is Latosol, the altitude is 525 metere above sea level. This research was arranged in Split-plot Design. Kinds of varieties as main plot concisted of 3 levelsPepe, Sintanur and IR 64, and dosages of NPK fertilizer as sub plot consisted 4 levels0 kg/ha, 200 kg/ha, 250 kg/ha and 300 kg/ha. In this research Urea.fertilizer was still used 200 kg/ha .The datas were analyzed using analysis variance and Least Significant Difference of 5% level. The research showed that kinds of varieties influenced .significant to high of plant, total amount of bough, amount of productive bough, dry shel of rice plant, dry shel of rice milled weight per sample, but not significant to weight of fresh straw and dry straw, dry shel of rice weight per plot, and weight of 1000 seeds. Dosages of NPR